Pituitary Apoplexy May Be Mistaken for Temporal Arteritis - Pedro, B (2019)
Pituitary apoplexy is a rare endocrine emergency, characterized by a sudden increase in pituitary gland volume secondary to acute ischaemic infarction or haemorrhage of the pituitary gland, usually in the presence of a pituitary adenoma. We present the case of a 79-year-old man admitted for new-onset, bi-temporal and severe headache, associated with photophobia and vomiting, whose additional study revealed pituitary apoplexy. This case highlights the need for high clinical suspicion of this rare entity in order to reduce the associated mortality.